MANAJEMEN PELAYANAN PUBLIK DALAM MENGATASI KENAIKAN HARGA BERAS DI INDONESIA - Nofindy Citra Danisma,; Amanda Ayu Febriana, (Juremi: Jurnal Riset Ekonomi, 2024)
The social problems faced by society today are related to the drastic increase in rice prices from previous prices. The increase in rice prices certainly affects the pattern of food consumption in the community. Grouping people based on income (low, medium and high) is done because income levels affect people's consumption patterns. This shows that the impact of rising rice prices will be addressed differently according to income level. The government still has not found a solution to the current rice price reduction. The purpose of the study was to determine the increase in rice prices in Indonesia.The study used secondary data.the process of searching for this data through internet media to obtain information based on journals and articles.the results showed that low-income groups are still more dependent on rice as a staple food than other community groups. The lower the income, the proportion of rice consumption will tend to increase and vice versa, the higher the income, the proportion of rice consumption will tend to decrease